2021
DOI: 10.1039/d1dt03579g
|View full text |Cite
|
Sign up to set email alerts
|

Inherently dinuclear iridium(iii) meso architectures accessed by cyclometalation of calix[4]arene-based bis(aryltriazoles)

Abstract: Conventional cyclometalation of calix[4]arene bis(aryltriazoles) with iridium(III) chloride hydrate leads to unique meso architectures in which the Ir2Cl2 core is cross-bound by two (C^N)2-ligands, that allows further replacement of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Unique photophysical properties of octahedral d 6 cyclometalated iridium complexes in combination with their high stability determine current and potential application of these complexes [1][2][3][4][5] in organic light emitting diodes (OLEDs), [6][7][8] photodynamic therapy and bioimaging, [9][10][11][12][13] as homogeneous photocatalysts, 14,15 biosensors, [16][17][18] building blocks for supramolecular architectures [19][20][21] and photosensitizers in dyesensitized solar cells (DSSC). [22][23][24][25][26][27] The latter technology is experiencing a renaissance, 28 being highly attractive for several niche applications (mostly indoors) for which diffuse light performance, transparency and flexibility are more important factors than the high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Unique photophysical properties of octahedral d 6 cyclometalated iridium complexes in combination with their high stability determine current and potential application of these complexes [1][2][3][4][5] in organic light emitting diodes (OLEDs), [6][7][8] photodynamic therapy and bioimaging, [9][10][11][12][13] as homogeneous photocatalysts, 14,15 biosensors, [16][17][18] building blocks for supramolecular architectures [19][20][21] and photosensitizers in dyesensitized solar cells (DSSC). [22][23][24][25][26][27] The latter technology is experiencing a renaissance, 28 being highly attractive for several niche applications (mostly indoors) for which diffuse light performance, transparency and flexibility are more important factors than the high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that two calix [4]arene cores could be readily linked to each other by two azobenzene or stilbene units using the K 2 CO 3promoted alkylation of parent calixarene tetrols with 4,4 -bis-bromomethylated azobenzene or stilbene, which furnished semi-tubular bis(calix [4]arenes) capable of shape changes upon irradiation/heating [32]. On the other hand, our ongoing studies on the features [33,34] and applications [35,36] of the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) in calixarene chemistry showed the great potential of this reaction for the preparation of diverse receptor molecules including bis-and triscalixarene semi-tubular assemblies [37,38] comprising 1,4-disubstituted 1,2,3-triazoles as the key linking or/and receptor units. Within a reasonable extension of the above studies, herein we investigated the applicability of the CuAAC approach for the one-step construction of biscalixarene molecules from the calix [4]arene dipropargyl ethers and bis-azidomethylated azobenzene or stilbene.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown 8 that diverse biscalixarene semi-tubes may be constructed from the respective bisazide and bisalkyne calixarene precursors using copper( i )-catalyzed azide–alkyne cycloaddition (CuAAC). 9 Each of these assemblies comprises a single binding site formed by two 1,4-disubstituted 1,2,3-triazole groups surrounded by the calixarene cores and targeted to transition cations. Herein we explored the applicability of this synthetic approach for the construction of larger semi-tubular assemblies having three calix[4]arene cores in their structures and possessing two bistriazole receptor sites separated from each other by the central 1,3-alternate calix[4]arene unit.…”
Section: Introductionmentioning
confidence: 99%